THE ROLE OF TECHNICAL AND VOCATIONAL EDUCATION IN YOUTH EMPOWERMENT AND POVERTY ALLEVIATION - Oviawe, Jane Itohan (Sokoto Educational Review, 2020)
This paper focuses on ways in which Technical and Vocational Education (TVE) can empower youths and alleviate poverty in Nigeria. One of the current issues that is receiving wide attention is education for self-reliance. TVE entails development of manpower skills needed for self-reliance by availing trainees the opportunity of acquiring appropriate skills, abilities and competences both mental and physical as equipment for the recipient to live and contribute to the development of the society. It will contribute to poverty alleviation and the sustainability of the social and economic development of Nigeria through job creation by requiring government attention to further enhance training opportunities. The paper also examined some challenges facing TVE in Nigeria, amongst which include: inadequate supply of technical teachers, inadequate finding, etc. it is recommended among others that to enhance the success of TVE programmes: Instructional facilities needed for effective teaching of should be adequately provided, TVE educators should be retrained on a continuous basis.